Strategi dan Implementasi Penyusunan Soal HOTS Kimia Berbasis Lesson Study - Moh Ismail Sholeh; Yeva Olensia (Orbital: Jurnal Pendidikan Kimia, 2022)
Higher Order Thinking Skill (HOTS) instrument tests are still rarely developed by teachers in assessment activities. The purpose of this study was to determine the strategy and implementation of lesson study-based HOTS chemistry questions in MAN OKU Timur. This research is action research by applying lesson study which includes the stages of planning, implementation, and reflection. The subjects of this study were 8 chemistry teachers at MAN OKU Timur. The instruments used in this study were interview guides, HOTS test sheets, and participant observation sheets for lesson study activities. Data analysis methods are data reduction, presenting data, drawing conclusions, and verification. The results showed that the strategy for preparing HOTS questions in MAN 1 OKU Timur was based on lesson study through the following activities: the preparation stage (plan) in the form of explaining the HOTS concept; the implementation stage (do) is in the form of steps for preparing basic competency analysis questions, compiling question grids, making stimulus and question indicators, making questions and scoring guidelines; the reflection stage (see) in the form of a discussion of the results of developing HOTS questions and solving problems that arise. The implementation of lesson study-based HOTS questions in MAN OKU Timur obtained a percentage of 87.25% with a very good category.